2009
DOI: 10.3342/ceo.2009.2.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-8 Expression in Laryngeal Squamous Cell Carcinoma

Abstract: ObjectivesDespite the ongoing development of treatment protocols for laryngeal squamous cell carcinoma (LSCC), the patients suffering with this malady have shown only a modestly improved outcome. This poor outcome has been attributed to the lack of therapy that's individualized to the tumor's biological properties. Various studies have showed that galectin-8 is widely expressed in tumor tissues as well as in normal tissues, and the level of the galectin-8 expression may correlate with the malignancy of human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Our data indicate that Treg cells polarized in the presence of Gal-8 are functional, as they are able to inhibit the proliferation of activated T cells. Gal-8 expression is upregulated in certain cancers, such as laryngeal squamous cell carcinoma and thyroid tumors 20,21. Thus, it is possible that in addition to its role in angiogenesis, 22 Gal-8 may promote tumor immune evasion and survival by stimulating Treg cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that Treg cells polarized in the presence of Gal-8 are functional, as they are able to inhibit the proliferation of activated T cells. Gal-8 expression is upregulated in certain cancers, such as laryngeal squamous cell carcinoma and thyroid tumors 20,21. Thus, it is possible that in addition to its role in angiogenesis, 22 Gal-8 may promote tumor immune evasion and survival by stimulating Treg cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Gal-8 expression is upregulated in certain cancers, such as laryngeal squamous cell carcinoma and thyroid tumors. 17,18 Thus, it is possible that in addition to its role in angiogenesis, 19 Gal-8 may promote tumor immune evasion and survival by stimulating Treg cell differentiation. Others have demonstrated that Gal-1 and Gal-9 positively regulate Treg cell function, 10,11 whereas Gal-3 negatively regulates Treg cell expansion and function.…”
Section: Gal-8 Promotes Treg and T H 2 Cell Differentiation And Inhimentioning
confidence: 99%
“…In a second study on colon cancer, the preliminary data could be confirmed in a larger cohort, suggesting a marked decrease of galectin-8 expression with more aggressive tumor types [8] . However, implied conflicting data appeared on laryngeal squamous cell carcinoma as, in contrast to Danguy et al, an increase with tumor and clinical stages was observed [20] . It must be explicitly noted that normal laryngeal tissue was not compared to tumor tissue.…”
Section: Discussionmentioning
confidence: 86%
“…Such signals are evidently read and interpreted by members of the family of adhesion/growth-regulatory galectins (16)(17)(18), and these bioeffectors are present in SCC. Their study was initiated in cells and immunohistochemically for galectins 1 and 3 (19-24), then extended to other family members such as galectins 7, 8 and 9, indicating the presence of a galectin network (25)(26)(27)(28)(29)(30)(31). At the level of cellular activity, the demonstration that a lectin such as galectin-1 is associated to pro-inflammatory/invasive activities such as those of chemo-and cytokines, or the prodegradative matrix metalloproteinases, points to a molecular bridge from lectins to tumor progression (32)(33)(34).…”
mentioning
confidence: 99%